DIFFERENCES IN TEENAGE GIRLS’ KNOWLEDGE AND ATTITUDE BEFORE AND AFTER BEING EXPOSED IN PUBLIC SERVICE ANNOUNCEMENT MEDIA OF "IRON SUPPLEMENTATION" (Study at SMP Negeri 10 Surabaya) - Yohana Nensy Lasamahu; Sri Widati (The Indonesian Journal of Public Health, 2022)
Introduction: Teenage girls are included in groups who are prone to anemia. Various attempts have been made to prevent anemia in teenage girls. Public service announcement of "Iron Supplementation" is one of the health promotion media related to the prevention of anemia. This research aims to determine the difference in the knowledge and attitudes of teenage girls before and after exposure to public service announcement media of "Iron Supplementation". Methods: This research is a quantitative study with pseudo-experimental methods. The knowledge and attitude variables are measured by the Paired T-test test and the Mann-Whitney test. The study subject amounted to 30 subjects for each group. Result: The results of the analysis show that there were differences in the students' knowledge (p = 0.00) before and after watching videos in both the "selfie" group and the "animation" group. There were differences in students' attitudes before and after watching the video on the "selfie" group         (p = 0.00). However, there was no difference in the student's attitudes toward the "animation" group (p= 0.469). Conclusion: There was no difference in students' knowledge between selfie groups and animation groups after watching videos. There was a difference in attitudes between the "selfie" group and the "animation" group after watching videos. Public service announcement is needed in delivering health messages for changes in knowledge and attitudes. However, there is still a need for mentoring and direct support from teachers